2003
DOI: 10.1007/s15010-003-3091-8
|View full text |Cite
|
Sign up to set email alerts
|

Influenza B Pneumonia with Staphylococcus aureus Superinfection Associated with Parvovirus B19 and Concomitant Agranulocytosis

Abstract: An 11-year-old patient with anamnestic fever for 3 days and signs of upper respiratory tract infection underwent fulminant Staphylococcus aureus pneumonia with concomitant agranulocytosis. From autopsia influenza B virus and parvovirus B19 were detected by nucleic acid amplification technique (NAT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Pulmonary complications such as primary viral pneumonia, secondary bacterial or fungal pneumonia, combined viral-bacterial pneumonia, and exacerbations of chronic pulmonary diseases have been described (Aebi et al, 2010; Chen et al, 2011; Gutierrez-Pizarraya et al, 2012; Krell et al, 2003; Paddock et al, 2012; Wang et al, 2009; Yusuf et al, 2007). Importantly, histological evidence of interstitial pneumonia and immunohistochemical features of alveoli involvements during influenza B virus infections was provided for fatal cases (Paddock et al, 2012).…”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%
“…Pulmonary complications such as primary viral pneumonia, secondary bacterial or fungal pneumonia, combined viral-bacterial pneumonia, and exacerbations of chronic pulmonary diseases have been described (Aebi et al, 2010; Chen et al, 2011; Gutierrez-Pizarraya et al, 2012; Krell et al, 2003; Paddock et al, 2012; Wang et al, 2009; Yusuf et al, 2007). Importantly, histological evidence of interstitial pneumonia and immunohistochemical features of alveoli involvements during influenza B virus infections was provided for fatal cases (Paddock et al, 2012).…”
Section: Epidemiology and Clinical Manifestation Of Infection Causmentioning
confidence: 99%
“…Previous studies often reported that cases of influenza A or B virus infection were complicated with simple fulminant pneumonia caused by S. aureus. However, the clinical characteristics of influenza virus infection complicated with both fulminant pneumonia and septicemia caused by S. aureus were rarely mentioned and described (6)(7)(8). In this report we describe two cases of fatal sepsis and pneumonia caused by PVL-MSSA, which was following influenza B infection in the immunocompetent patients.…”
Section: Introductionmentioning
confidence: 81%
“…But to our knowledge, this is the first report of fatal fulminant pneumonia and septicemia in China in which co-incident infection with both influenza B and PVL-positive MSSA was laboratory confirmed. Several reports indicated that influenza virus infection results in epithelial cell injury and facilitates the occurrence of secondary bacterial infection through multiple mechanisms of immunological injury (3,(6)(7)(8)(9). The hypothesis of immunological injury caused by the influenza virus B in the host includes decreased bacterial phagocytosis among alveolar macrophages, downregulated expression of toll-like receptors, and functional inhibition of neutrophil recruitment by type I interferon initiated by the viral infection (10).…”
Section: Discussionmentioning
confidence: 99%
“…These 2 infections have been shown to act synergistically in animal models to induce a rapidly progressive necrotizing pneumonia associated with severe leukopenia ( 7 ). This is unlike classic secondary bacterial pneumonia, which typically occurs in a biphasic course with influenza ( 2 ). …”
mentioning
confidence: 96%
“…Bacterial pneumonia with Panton-Valentine leukocidin-producing (PVL) Staphylococcus aureus is infrequently described in the literature as occurring concurrently with influenza B virus infection ( 2 4 ). Additionally, only 2 occurrences of peripartum PVL-methicillin-resistant S. aureus (MRSA) pneumonia have been described ( 5 , 6 ).…”
mentioning
confidence: 99%